The association between age of menopause and type 2 diabetes: a systematic review and meta-analysis - Mansoureh Yazdkhasti; Kyana Jafarabady; Arman Shafiee; Samira Parvizi Omran; Zohre Mahmoodi; Sara Esmaeilzadeh; Touran Bahrami Babaheidari; Kourosh Kabir; Maral Peisepar; Mahmood Bakhtiyari (Nutrition & Metabolism)
Abstract Background Type-2 diabetes mellitus (T2DM) is considered one of the chronic diseases that can have a relationship with age of menopause onset. Several studies have revealed that early menopause or late menopause can have a correlation with type-2 diabetes. This systematic review and meta-analysis aimed to investigate the association between the age of menopause onset and type-2 diabetes. Methods and materials PubMed, Web of Science, Scopus, Science Direct, Google Scholar, and Cochrane were searched for studies that have evaluated the relationship between T2DM and age of menopause onset. We pooled the effect sizes of the included studies using both adjusted odds ratios (OR) and hazard ratios (HR) of interest outcomes with their 95% confidence interval (CI). Results Nineteen papers were included in this study, 8 studies were cohorts, and 11 were cross sectional. Studies revealed a statistically significant association between early menopause age and increased odds of T2DM (OR = 1.24, 95% CI: 1.09–1.40; I2 = 67%; p = 0.001). Late menopause age was also associated with an increased odds of T2DM (OR = 1.14, 95% CI: 1.03–1.26; I2 = 56%; p = 0.01) compared to the reference group with normal menopausal age. As our secondary outcome, the hazard of developing T2DM in individuals with early or late menopausal age was assessed. Pooled analysis demonstrated a significantly higher hazard of T2DM among women with early menopause age (HR = 1.31, 95% CI: 1.05–1.64; I2 = 72%; p = 0.02). Late menopause age did not show a significant association (HR = 0.96, 95% CI: 0.84–1.10; I2 = 68%; p = 0.56). Conclusion Early and late menopause can both increase the risk of T2DM. Future research is needed to warrant the certainty of our findings.